2014
DOI: 10.2174/1871520614666140209144042
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caspases, Bax and Bcl-2 in Chrysin-Induced Apoptosis in the A549 Human Lung Adenocarcinoma Epithelial Cells

Abstract: This study shows that chrysin could also be considered as a promising chemotherapeutic agent and anticancer activity in treatment of the lung cancer cells in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…For the cells treated with chrysin, cells stained with DAB (indicating apoptotic changes) were significantly increased compared to the controls. This is consistent with previous studies, which have reported an apoptosis-induction effect of chrysin in prostate cancer, lung cancer, leukemia and cutaneous melanoma cells (4,5,9,12).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…For the cells treated with chrysin, cells stained with DAB (indicating apoptotic changes) were significantly increased compared to the controls. This is consistent with previous studies, which have reported an apoptosis-induction effect of chrysin in prostate cancer, lung cancer, leukemia and cutaneous melanoma cells (4,5,9,12).…”
Section: Discussionsupporting
confidence: 94%
“…However, the activities of caspase-8 were not altered following treatment with chrysin. These observations are consistent with previous reports (9,12), that suggested that chrysin induced apoptosis in cutaneous melanoma cells and lung adenocarcinoma epithelial cells primarily via the intrinsic mitochondrial signaling pathway.…”
Section: A B Csupporting
confidence: 94%
See 2 more Smart Citations
“…The effect of Bcl-2 depends on the ratio of its expression with Bax; this ratio determines whether cells undergo apoptosis or survival upon signal stimulation (35). Excessive Bax expression in cells promotes apoptosis, whereas excessive Bcl-2 expression promotes survival (36).…”
Section: Discussionmentioning
confidence: 99%